Analisis Kepribadian Tokoh Utama Pada film “The Miracle Worker” - Nur Fauziah Fatawi (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2019)
This study aims to determine, analyze and describe the psychological complexity of the main character in the film "The Miracle Worker" with a focus on the study of id, ego and super ego. Researcher used Sigmund Freud's psychoanalytic theory to examine the main character named Hellen Keller. This type of research is a qualitative study with the results of the analysis presented in a descriptive narrative. The results of this study are the Id in Hellen Keller is driven by a big desiring to do things like humans in general, like hearing, having eyes, being able to talk, but they all she could not do, so she felt upset. While her ego has made her often easy to be angry, difficult to manage, naughty, spoiled, disrespectful, and sometimes also do anything that makes her happy, even though it is wrong. Her super ego made her never give up, keep trying when taught through a hand code, and smart because it can immediately imitate, and envy to be taught knowledge when she also has a good superego, when Mrs. Sullivan only taught Percy only and Hellen did not.